Rosiglitazone, a Ligand to PPARγ, Improves Blood Pressure and Vascular Function through Renin-Angiotensin System Regulation - María Sánchez-Aguilar; Luz Ibarra-Lara; Leonardo Del Valle-Mondragón; María Esther Rubio-Ruiz; Alicia G. Aguilar-Navarro; Absalom Zamorano-Carrillo; Margarita del Carmen Ramírez-Ortega; Gustavo Pastelín-Hernández; Alicia Sánchez-Mendoza (PPAR Research)
Rosiglitazone (RGZ), a peroxisome proliferator-activated receptor gamma (PPARγ) ligand, has been reported to act as insulin sensitizer and exert cardiovascular actions. In this work, we hypothesized that RGZ exerts a PPARγ–dependent regulation of blood pressure through modulation of angiotensin-converting enzyme (ACE)-type 2 (ACE2)/angiotensin-(1-7)/angiotensin II type-2 receptor (AT2R) axis in an experimental model of high blood pressure. We carried on experiments in normotensive (Sham) and aortic coarctation (AoCo)-induced hypertensive male Wistar rats. Both sham and AoCo rats were treated 7 days with vehicle (V), RGZ (5 mg/kg/day), or RGZ+BADGE (120 mg/kg/day) post-coarctation. We measured blood pressure and vascular reactivity on aortic rings, as well as the expression of renin-angiotensin system (RAS) proteins. We found that RGZ treatment in AoCo group decreases blood pressure values and improves vascular response to acetylcholine, both parameters dependent on PPARγ-stimulation. RGZ lowered serum angiotensin II (AngII) but increased Ang-(1-7) levels. It also decreased 8-hydroxy-2′-deoxyguanosine (8-OH-2dG), malondialdehyde (MDA), and improved the antioxidant capacity. Regarding protein expression of RAS, RGZ decreases ACE and angiotensin II type 1 receptor (AT1R) and improved ACE2, AT2R, and Mas receptor in AoCo rats. Additionally, an in silico analysis revealed that 5′UTR regions of RAS and PPARγ share motifs with a transcriptional regulatory role. We conclude that RGZ lowers blood pressure values by increasing the expression of RAS axis proteins ACE2 and AT2R, decreasing the levels of AngII and increasing levels of Ang-(1-7) in a PPARγ-dependent manner. The in silico analysis is a valuable tool to predict the interaction between PPARγ and RAS.